Zein–sodium caseinate–diosmin nanoparticles as a promising anti-cancer agent with targeted efficacy against A2780 cell line - Mahmoud Faezi; Alireza Motavalizadehkakhky; Masoud Homayouni Tabrizi; Samaneh Dolatabadi; Ali Es-haghi (Scientific Reports)
Abstract This research investigated the potential of zein–sodium caseinate–diosmin nanoparticles (ZCD-NPs) as an anti-cancer agent against the A2780 cell line. Dynamic light scattering (DLS) analysis showed that ZCD-NPs have an average size of 265.30 nm with a polydispersity index of 0.21, indicating good uniformity suitable for pharmaceutical applications. Fourier transform infrared spectroscopy (FTIR) confirmed the successful incorporation of diosmin into the NPs and highlighted the interactions between the components. Field emission scanning electron microscopy (FESEM) images showed spherical NPs with smooth surfaces, suggesting stability and high production quality. Encapsulation efficiency was remarkably high, at 93.45%. Cytotoxicity assays showed a dose-dependent effect of ZCD-NPs, with A2780 cells showing significant sensitivity compared to normal HDF cells, indicating selective targeting of cancer cells. Flow cytometry analysis confirmed that ZCD-NPs induced apoptosis and necrosis in A2780 cells, as evidenced by increased expression of apoptotic genes such as p53 and caspases 8 and 9. In addition, ZCD-NPs exhibited potent antioxidant activity, effectively scavenging free radicals. These results suggest that ZCD-NPs have promising properties for targeted cancer therapy and antioxidant applications, which warrant further exploration in clinical settings.